Chapter Le conseguenze economiche dell'innovazione bellica. La produzione di «artiglierie alla francese» a Firenze tra Quattro e Cinquecento - ANSANI, FABRIZIO ANTONIO (Datini Studies in Economic History, 2023)
The paper aims to assess the financial impact of the rapid assimilation of the French-style artillery into Italian warfare. The focus will be on the policy adopted by the Florentine Republic to improve the efficiency of its logistic system during the War of Pisa (1494-1509): through the analysis of public records, the research will highlight the significant transformations occurred in late medieval military industry, reevaluating the importance of the trade in strategic materials for the early modern economy and demonstrating the concerted effort made by the rising renaissance state to establish a monopoly on the manufacture of arms and «munitions».